PLANNING EVALUATION OF ROADSIDE SERVICE STATION PROVISION TO SUPPORT TOURISM SECTOR IN WEST JAVA PROVINCE (Case Study: Kamojang Tourism West Bandung Regency) - Hendrawan, Hendra (Creative Research Journal, 2018)
Road infrastructure is an important part of economic development. Problem related to land transport today are safety issues and ineffectively of road infrastructure to boost economic growth. To address the issue of road safety and enhancing the role of road infrastructure in develeping economic sector, appropriate infrastructure is needed, one of them is through providing rest area with roadside service station concept. To reduce the accident number due to driver fatique and vehicle problem, and to to support the Kamojang geo-tourism sector, Government of Bandung Regency intends to provide rest area at Cukang Monteng Ibun road segments. This study aims to analyze the suitability of site selection and fulfillment of the criteria that has set in the guideline of Planning Rest Area on Public Roads. The method used to analysis are Method of Context Analysis and Comparative Analysis.From the analysis result obtained the conclusion that the choice of rest area location was appropiate, but the were still some criteria that need to be followed up in order the providing of rest area optimaly and sustainable